An investigation of methanol and inorganic bromides for thermally operated heat pumps - El-Shamarka, S. (Cranfield University, 1981)
Working fluids for thermal heat pump cycles have been studied. Methanol in conjunction with a mixture of inorganic bromides has been identified as being suitable for transforming heat from temperatures below zero centigrade. A computer programme was written in order to calculate the performance of such a combination, and its accuracy was verified by comparing its predictions with the actual performance of existing (commercial) heat pumps and chillers using combinations other than the above. Transport and other properties of the mixture have been measured, including vapour pressure, specific heat, viscosity, relative density, solubility, thermal conductivity, surface tension, heat of absorption, absorption coefficient, and hence mass diffusivity. An intermittent absorption heat pump was constructed and its performance measured. The tests demonstrated that it was capable of pumping heat from -10 °C up to 74 °C.